2012
DOI: 10.1186/1750-2187-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor receptor TrkB exists as a preformed dimer in living cells

Abstract: BackgroundNeurotrophins (NTs) and their receptors play crucial roles in the development, functions and maintenance of nervous systems. It is widely believed that NT-induced dimerization of the receptors initiates the transmembrane signaling. However, it is still controversial whether the receptor molecule has a monomeric or dimeric structure on the cell surface before its ligand binding.FindingsUsing chemical cross-linking, bimolecular fluorescence complementation (BiFC) and luciferase fragment complementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
2
31
1
Order By: Relevance
“…However, an increasing number of studies demonstrate that RTKs exist as pre-formed, yet inactive, dimers, even in the absence of activating ligand [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. IR and IGF-IR are also expressed as disulfide-linked (αβ) 2 homodimers at the cell surface [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, an increasing number of studies demonstrate that RTKs exist as pre-formed, yet inactive, dimers, even in the absence of activating ligand [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. IR and IGF-IR are also expressed as disulfide-linked (αβ) 2 homodimers at the cell surface [30].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when Torso was expressed alone we saw an almost twofold increase in reporter activity relative to vector control. Although some receptor tyrosine kinases remain in a monomeric state until binding of ligand leads to dimerization (Ullrich and Schlessinger, 1990;Lemmon and Schlessinger, 2010), others are present in an inactive dimeric state with a conformation in which the intracellular domains of the two proteins are unable to interact productively in the absence of ligand (Ward et al, 2007;Tao and Maruyama, 2008;Shen and Maruyama, 2012). Recently, it has been reported that B. mori Torso expressed in Drosophila S2 cells undergoes ligand-independent dimerization via disulfide linkages formed by cysteine residues present in the transmembrane domain (Konogami et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether dimerization of Torso in response to Trk or Tsl could be detected in our system, we used bimolecular fluorescence complementation (BiFC) (Hu et al, 2002;Kodama and Hu, 2010;Tao and Maruyama, 2008;Shen and Maruyama, 2012), a method for visualizing interactions between proteins via dimerization-mediated complementation of split fluorescent proteins. We generated constructs to express wild-type and Torso (Fig.…”
Section: Both Trk and Tsl Promote Torso Dimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…pBiFC-TrkB-FL and pBiFC-TrkB-Δ-ICD constructs were kindly provided by Dr Maruyama, Okinawa Institute of Science and Technology, Japan [39]. These constructs were transfected into primary cortical neurons using Effectene Transfection Reagent (Qiagen) 48 h before NRG1 treatment.…”
Section: Trkb Deletion Plasmidsmentioning
confidence: 99%